Implementasi Pembelajaran Ilmu Pengetahuan Sosial Berbasis Kearifan Lokal Dan Moderasi Beragama - Laily Fu'adah; Noor Fatmawati; Fifi Nofiaturrahmah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
To make it easier for students to understand the material, teachers can carry out learning activities by utilizing the surrounding environment. Such as learning based on local wisdom wrapped in the values of religious moderation. The purpose of this study was to determine the implementation of social studies learning based on local wisdom and religious moderation at Madrasah Tsanawiyah, Wirosari District. The research design uses qualitative research methods. Collecting data using interview techniques, observation and documentation. The results of this study are that there is social studies learning based on local wisdom and moderation of religion at MTs Wirosari Subdistrict which is listed in the RPP which contains the integration of local wisdom and religious moderation that takes place during the learning process. The character values contained in the implementation of Social Studies learning based on local wisdom are religious values, mutual cooperation values, historical values, and economic values, while the character values based on Religious Moderation are tasamuh, tahadhdhur, and tawazun attitudes. Then the relevance of social studies learning based on local wisdom can be seen in the lesson plan which contains the integration of local wisdom and the concept of religious moderation in social studies learning materials, namely Basic Competency 3.1 and 4.1 in class VII and class VIII. It is hoped that by implementing local wisdom-based learning and religious moderation in social studies learning, it will be able to provide students with a more comprehensive understanding.Key word : Learning Social Sciences, Local Wisdom, Religious Moderation